Developing Quality Social Relationships: Technology-Based Learning Model to Enhance Social Skills in Boarding Schools - Fadhila Aisyah Nurunisa; Sadam Fajar Shodiq (Journal of Innovation in Educational and Cultural Research, 2024)
The technology-based learning process is one of the innovations in teaching and learning, one of which is in boarding schools. The aim is to find the effect of technology-based learning (X) in improving students' social skills at boarding school (Y). This research used a quantitative method using a Likert scale survey processed by Smart-PLS software. The research sample was 298 students from 4 boarding schools in Yogyakarta. The research results show a positive impact of technology-based learning on students' social abilities; many students are confident and shrewd even though technology continues to develop. They can align learning with online media. Apart from this research, it is hoped that many schools, especially boarding schools, will start implementing learning technology-based and not limit student interaction at school. Learning by utilizing online media is a collaboration and success in applying technology in education.